2002
DOI: 10.1073/pnas.022628899
|View full text |Cite
|
Sign up to set email alerts
|

Ca 2+ -desensitizing effect of a deletion mutation ΔK210 in cardiac troponin T that causes familial dilated cardiomyopathy

Abstract: A deletion mutation ⌬K210 in cardiac troponin T (cTnT) was recently found to cause familial dilated cardiomyopathy (DCM). To explore the effect of this mutation on cardiac muscle contraction under physiological conditions, we determined the Ca 2؉ -activated force generation in permeabilized rabbit cardiac muscle fibers into which the mutant and wild-type cTnTs were incorporated by using our TnT exchange technique. The free Ca 2؉ concentrations required for the force generation were higher in the mutant cTnTexc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
114
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 46 publications
14
114
1
Order By: Relevance
“…The functional changes caused by cTnT mutation in DCM appear to be opposite from those induced by fHCM-related cTnT mutations. This suggests that the primary mechanism for the pathogenesis of cTnT mutation-associated DCM is a deficiency of force generation, which is in contrast to the enhancement of force generation in fHCM associated with other mutations in cTnT (228). However, the role of Ca 2+ sensitization/desensitization in myopathies is still not completely understood.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 58%
See 1 more Smart Citation
“…The functional changes caused by cTnT mutation in DCM appear to be opposite from those induced by fHCM-related cTnT mutations. This suggests that the primary mechanism for the pathogenesis of cTnT mutation-associated DCM is a deficiency of force generation, which is in contrast to the enhancement of force generation in fHCM associated with other mutations in cTnT (228). However, the role of Ca 2+ sensitization/desensitization in myopathies is still not completely understood.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 58%
“…Morimoto et al (228) have also recently reported a similar decrease in Ca 2+ sensitivity in rabbit heart trabeculae when endogenous troponin was replaced with human cTnT (either wild type or mutant). The decreased Ca 2+ sensitivity, together with the decreased crossbridge turnover rate and reduced cooperativity, suggests that the expression and incorporation of this DCM-related cTnT mutant in vivo may result in myofilaments that are markedly less responsive to Ca 2+ , contract more slowly and thus are unable to produce sufficient force during activation (213,228).…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…2). Morimoto et al (11) postulated that a decrease in Ca 2ϩ sensitivity was the main cause of DCM. However, the results from the TnT-R141W mutant suggest that this may not be the case for all TnT-DCM mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have investigated the functional consequences of the DCM-causing TnT mutations R141W, ⌬K210, and K273E on the regulatory properties of the thin filament. Previously, Morimoto et al (11) investigated TnT-⌬K210 and hypothesized that the Ca 2ϩ desensitizing effect of this mutation is the primary cause of dilated cardiomyopathy. Because Ca 2ϩ is the primary activator of the thin filament, we investigated how this mutation affects the Ca 2ϩ sensitivity of force development.…”
mentioning
confidence: 99%
“…14,15 It is noteworthy that mutations in the components of thin filaments that cause DCM are associated with decreased Ca 2ϩ sensitivity of the myofibrillar ATPase activity, force generation, or both. 16,17 It is intriguing to postulate that the impact of the thin filament mutations on Ca 2ϩ sensitivity of myofibrillar force generation, ATPase activity, or both is the main determinant of the ensuing phenotype being DCM or HCM. Ca 2ϩ sensitivity of myofibrils is probably determined by the impact of mutation on the affinity of the inhibitory arm of cTnI for the ␣-tropomyosin-actin complex.…”
Section: See Pp 2330 and 2339mentioning
confidence: 99%